2007
DOI: 10.1080/10934520701480953
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic ecotoxicology approaches in Western Mexico

Abstract: A series of bioindicator organisms for aquatic ecosystems are being maintained under laboratory conditions in order to analyze effects of pollution on aquatic wildlife and potential effects on human health. Growth kinetics of algae Pseudokirchneriella subcapitata was used to evaluate effects of the surfactant nonilphenol (NP). Brachionus calyciflorus was used to set up a model of endocrine disruption using the fungicide vinclozolin (Vc). We exposed salamanders from the genus Ambystoma sp., to different concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Whether the latter is true or not, the present results could confirm the importance of studying complete agrochemical formulations in toxicity screenings because the excipient(s) may have toxicological properties completely different from those of the active ingredients alone, and their impacts may be quite different, as demonstrated previously in different biotic matrices (Cox and Surgan, 2006;González et al, 2007;Nikoloff et al, 2012;Soloneski and Larramendy, 2010). The SCGE test has become extensively valuable as a biomarker in amphibians to monitor contaminated areas (in situ assay) (Burlibasa and Gavrila, 2011;Maselli et al, 2010;Ralph and Petras, 1998) as well as for screening xenobiotics after direct or indirect exposure (in vivo assay) (Binelli et al, 2009;Knakievicz et al, 2008;Mouchet et al, 2007;Zavala-Aguirre et al, 2007). We observed that, regardless of the concentration, acute exposure to Twin Pack Gold s or Rainbow s increased the frequency of primary DNA lesions estimated by alkaline SCGE, a result opposite that of the MN test.…”
Section: Discussionmentioning
confidence: 93%
“…Whether the latter is true or not, the present results could confirm the importance of studying complete agrochemical formulations in toxicity screenings because the excipient(s) may have toxicological properties completely different from those of the active ingredients alone, and their impacts may be quite different, as demonstrated previously in different biotic matrices (Cox and Surgan, 2006;González et al, 2007;Nikoloff et al, 2012;Soloneski and Larramendy, 2010). The SCGE test has become extensively valuable as a biomarker in amphibians to monitor contaminated areas (in situ assay) (Burlibasa and Gavrila, 2011;Maselli et al, 2010;Ralph and Petras, 1998) as well as for screening xenobiotics after direct or indirect exposure (in vivo assay) (Binelli et al, 2009;Knakievicz et al, 2008;Mouchet et al, 2007;Zavala-Aguirre et al, 2007). We observed that, regardless of the concentration, acute exposure to Twin Pack Gold s or Rainbow s increased the frequency of primary DNA lesions estimated by alkaline SCGE, a result opposite that of the MN test.…”
Section: Discussionmentioning
confidence: 93%
“…Although, much higher toxicity has been reported for the aquatic microcrustacean D. magna (Kusk, 1996) as well as for the mosquito C. quinquefasciatus (Magnin et al, 1988), with an EC-50 of 0.014 mg L À1 and an LC-50 24 h of 8.5 mg L À1 , respectively. The MNi test has been extensively applied as an end-point for genotoxicity in amphibians (Wirz et al, 2005;Huang et al, 2007;Peltzer et al, 2008) to monitor contaminated areas (in situ assay) as well as for screening different compounds after direct or indirect exposure (in vivo assay) (Lajmanovich et al, 2005;Mouchet et al, 2007;Zavala-Aguirre et al, 2007;Binelli et al, 2008Binelli et al, , 2009Knakievicz et al, 2008). In 1986, Jaylet and coworkers (1986) described a model micronucleus test system using peripheral blood erythrocytes from the new larvae of Pleurodeles waltl for detecting mutagens in water pollution.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, reliable and practical methods that detect the presence of genotoxic contaminants are scarce [ 4 ]. The micronucleus assay is commonly used for evaluating structural and numerical chromosomal aberrations caused by clastogenic and aneugenic agents [ 5 , 6 , 7 , 8 ], and it was originally developed in mammals [ 5 , 9 , 10 , 11 , 12 ]; however, it has been successfully adapted to other non-mammalian organisms, such as fish erythrocytes [ 13 ], amphibian larvae [ 14 , 15 ], and the shed skin of salamanders [ 16 ], among others.…”
Section: Introductionmentioning
confidence: 99%